2021
DOI: 10.1186/s12929-021-00735-5
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 7 mediates endothelin-1-induced connective tissue growth factor expression in human lung fibroblasts through p300 and activator protein-1 activation

Abstract: Background Histone deacetylase (HDAC) inhibition was reported to ameliorate lung fibrosis in animal models. However, little is known about the underlying mechanism of HDAC7 in the regulation of CTGF production in lung fibroblasts. Methods The role of HDAC7 in CTGF production caused by ET-1 stimulation in WI-38 cells (human lung fibroblast) was examined. We also evaluated the expression of HDAC7 in the lung of ovalbumin-induced airway fibrosis model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In detail, endothelin-1 promoted HDAC7 translocation from the cytosol to nucleus and HDAC7 initiated AP-1 transcriptional activity (surprisingly) through the recruitment of p300 and consequent p300-mediated AP-1 acetylation. Conversely, RNAi-mediated silencing of either HDAC7 or EP300 suppressed endothelin-1-induced CTGF expression [296]. Taken together, these results indicate a crucial role for HDAC7 in cytokine/growth factor-induced expression of profibrotic molecules during fibrogenesis.…”
Section: Class Iia Histone Deacetylases In Ipf: Expression Profile Fu...mentioning
confidence: 80%
“…In detail, endothelin-1 promoted HDAC7 translocation from the cytosol to nucleus and HDAC7 initiated AP-1 transcriptional activity (surprisingly) through the recruitment of p300 and consequent p300-mediated AP-1 acetylation. Conversely, RNAi-mediated silencing of either HDAC7 or EP300 suppressed endothelin-1-induced CTGF expression [296]. Taken together, these results indicate a crucial role for HDAC7 in cytokine/growth factor-induced expression of profibrotic molecules during fibrogenesis.…”
Section: Class Iia Histone Deacetylases In Ipf: Expression Profile Fu...mentioning
confidence: 80%
“…CTGF expression is regulated through the epigenetic modification of DNA, such as histone acetylation [ 12 ]. In our previous study, HDAC7 regulated ET-1-induced CTGF expression through the activation of AP-1 in WI-38 cells [ 22 ]. In this study, we evaluated the role of HDAC2 and HDAC7 in ET-1-induced histone H3 acetylation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study indicated that ET-1 stimulates the expression of CTGF through the ET A R/JNK/AP-1 signaling pathway and that CTGF is required for ET-1-stimulated myofibroblast differentiation [ 53 ]. Moreover, ET-1 activates p300 and HDAC7 to initiate AP-1 transcriptional activity and eventually promotes the expression of CTGF [ 22 ]. In this study, we found that ET-1 increased HDAC2 phosphorylation through MAPKs and then induced the dissociation of the HDAC2/Sin3A/MeCP2 corepressor complex from the CTGF promoter region, which in turn promoted histone H3 acetylation, thus increasing CTGF expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sodium butyrate (NaBu) significantly attenuates Ang-II-induced cardiac hypertrophy and fibrosis, and inflammation by inhibiting the activation of the COX2/PGE 2 pathway in HDAC5/HDAC6-dependent manner [ 69 ]. The other members of Class II HDACs have been sparsely studied in cardiac fibrosis, but have been discovered to be associated with other organ fibrosis models [ 85 , 86 , 87 , 88 ].…”
Section: Histone Modification In Cfs Activation and Cardiac Fibrosismentioning
confidence: 99%